Upaya Pengurus OSIS Dalam Mengatasi Konflik Antara Anggota Osis Di SMA 4 Jember - Ningsih, Dwi Wahyu; Halizah, Siti Nur; Aldanty, Fajrina Zameilia; Zuhro’ Fitriana, Ani Qotuz (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
Consciously or not, a conflict can occur anywhere and in any sudden situation, an indication that may indicate that when a communication and information system does not meet a goal, it can result in a misunderstanding between two or more parties. Conflict is a conflict between winning or losing both between individuals and within a group. Conflict can also result in triggering a dispute between fellow members of the student council. However, besides the size of the problem of the conflict itself, conflict can also be resolved in many ways. For example, by choosing a middle way, and communicating well, and being calm between one another. The purpose of the research contains conflict in the behavior of an organization and the model of the way of resolution used by the student council members at SMA Negri 4 Jember in dealing with conflict, along with performance and productivity organization after the conflict at SMA Negeri 4 Jember City. This research is qualitative by using a naturalistic approach. Data collected through an observation, in-depth interviews and documentation studies. The data source consisted of the student council president and several student council members who knew the conditions of the conflict that occurred. The results of the research produced a result, that mediating conflicts, explaining the importance of a teamwork between osis members, emphasizing shared interests, conducting team building sessions, etc. are not easy enough to resolve a conflict that occurs. Therefore, transformational leadership is needed through an emotional intelligence approach, prioritizing a work ethic. In order for a similar conflict that will not occur again, the osis members must have a strong commitment, provide an opportunity, and encourage all elements of the osis members at SMA Negeri 4 Jember to work together on the basis of a noble value system, so that they are willing and without coercion, optimally participate in achieving ideal goals within the organization.